1986
DOI: 10.1037/h0079861
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Canadian applied psychological research to correctional and psychiatric institutions.

Abstract: Psychological research done in Canada and relevant to the treatment of persons institutionalized in psychiatric and correctional settings is reviewed. Studies are divided into four categories: prevention, assessment, treatment, and release. Although some innovative and influential applied research has been accomplished, the amount of applied research is relatively small and tends to focus on assessment rather than treatment issues. A discussion of some of the factors responsible for the relative paucity of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 174 publications
0
5
0
Order By: Relevance
“…A comprehensive review of the area completed by Rice and Quinsey (1986) shows that most of the research in correctional and psychiatric institutions completed in Canada emphasizes assessment and treatment issues. As the authors point out, however, psychology could have a greater impact in the area of corrections if researchers and practitioners would expand the realm of their interests.…”
Section: Criminal Justice System Researchmentioning
confidence: 99%
“…A comprehensive review of the area completed by Rice and Quinsey (1986) shows that most of the research in correctional and psychiatric institutions completed in Canada emphasizes assessment and treatment issues. As the authors point out, however, psychology could have a greater impact in the area of corrections if researchers and practitioners would expand the realm of their interests.…”
Section: Criminal Justice System Researchmentioning
confidence: 99%
“…The breadth of service of clinical psychology is rapidly expanding and clinical psychologists are making important contributions to our general hospitals (Arnett, Martin, Streiner, & Goodman, 1987) and medical schools (Arnett & Martin, 1981). Moreover, increasing numbers of psychologists are involved in "nontraditional" specialties such as health psychology (Lacroix, 1987), pain management (von Baeyer & Genest, 1985), custody and access mediation (Jaffe & Cameron, 1984), forensic services (Bonta, Cormier, Peters, Gendreau, & Marquis, 1983; Rice & Quinsey, 1986), and services for young offenders (Jaffe, Leschied, Sas, & Austin, 1985).…”
mentioning
confidence: 99%
“…By 1967, it was reported that Solicitor-General Pennell 'needed more psychiatrists in the Canadian Penitentiary Service' because the penitentiary was 'not a place to punish' but rather 'a place to reform and rehabilitate, to reduce crime by correcting antisocial attitudes' (Waring 1967, p.980). 'Correctional psychology' was an integral component of the overall correctionalist view of criminality prevalent in society during this time period (Bonta et al 1983;Rice and Quinsey 1986). This is why the experimental use of therapeutical drugs and experimental treatments was common practice in the 1950s, 1960s, and early 1970s.…”
Section: Correctional Philosophymentioning
confidence: 99%